Exploring the Cultivation Path of Chinese Ethnic Community Consciousness among College Students - Wang, Yawen (Journal of Theory and Practice of Social Science, 2023)
With the rapid development of China's social economy, the group of college students has played an undeniable role in national construction. On the one hand, they are the successors and inheritors of the cause of socialism with Chinese characteristics; On the other hand, they also face various challenges. Therefore, it is of great significance to strengthen the cultivation and identification of national community consciousness and promote contemporary college students to practice the Chinese national community consciousness. Based on the analysis of the current situation and existing problems of quality education for college students, this article proposes corresponding countermeasures and suggestions, aiming to promote the development process of traditional Chinese culture in Chinese universities and enhance the influence of the excellent spirit of the Chinese nation in the whole society through research.